Quality of life and persistent symptoms in patients with post-covid syndrome (Revista Contexto & Saúde, 2025)
Introduction: "Post-COVID-19 syndrome" refers to the persistence of physical and mental symptoms after the acute phase of the disease. These symptoms affect the individual's well-being, modifying his relationship with and perception of social and cultural contexts. Objective: To investigate how COVID-19 and its sequelae affected the individual's quality of life. Method: The research was divided into two phases: retrospective and observational cross-sectional analysis. The retrospective cross-sectional analysis consisted of analyzing the medical records of patients admitted to a hospital in the city of São Paulo, while the observational phase consisted of conducting structured interviews via telephone within one year after hospital discharge. Results: Data from 103 respondents were analyzed, of which 65% had pulmonary involvement, 52% were admitted to the ward, 39% to the ICU, and 53% were intubated. The most common persistent symptoms were muscle weakness (74.8%), dyspnea (61.2%), and loss of taste (48.5%), loss of smell (45.6%), desaturation (35.9%), and oxygen dependence (11.7%). Regarding quality of life, the environmental domain had the lowest score (~15%). Conclusion: More than half of the individuals developed persistent symptoms, a condition that affected quality of life, especially in the environmental domain, making it difficult to return to work and leisure activities.
Keywords: COVID-19; Symptom Assessment; Behavioral Symptoms; Quality of Life